Action research: Changing history for people living with dementia in New Zealand. Issue 1 (March 2014) - O'Sullivan, Grace; Hocking, Clare; Spence, Deb
Action research methods were underpinned by critical hermeneutic philosophy to uncover and interpret the support needs of people living with dementia in New Zealand. This involved 11 people with mild to moderate dementia and their primary caregiver in a collaborative process with the researcher. Data collection and analysis were reciprocally integrated, and the participants engaged in the production of knowledge. Coded data generated categories, the adequacy of which was judged by participants to clarify emerging understandings. The participants concluded that the historically rooted understandings of dementia in New Zealand needed to change. Dynamic involvement by the researcher at political, professional and community levels was informed by Kögler's (1999) version of critical hermeneutics. The actions evolving from the study contributed to significant changes that are occurring in New Zealand's health care system with regards to people with dementia. These outcomes highlight the value of engaging with critical hermeneutic philosophy.